Nature of Civil Society Engagement in Environmental Movement in Bangladesh: From the Perspective of NGOs’ Self-Evaluation - Saha, Labonno; Tasnim, Farhat (Asia Social Issues, 2025)
Civil society is engaged in different developmental activities to ensure a sustainable environment in developing countries. Observers can see civil society participating in the environmental movement at both national and international levels in the South. Bangladesh is one of the most environmentally vulnerable developing countries and civil society may be actively involved in environmental protection, management, and development. The present study aims to trace the nature of civil society engagements in the environmental movement in Bangladesh. The study is qualitative research. Researchers analyzed data from a survey on 25 environmental civil society organizations, 10 key informant interviews (KIIs), and newspaper reports. Civil society activities have been analyzed particularly from three levels: policy level, media level, and grassroots level. The study findings show that civil society’s involvement in environmental issues is more vivid at the grassroots and media levels than at the policy levels. Their influence on whether central or local political decisions are very weak. Civil Society needs to empower its capacity to play a decisive role in environmental policy decisions and the policy implementation process.